Multi‐decade tree mortality in temperate old‐growth forests of Europe and North America: Non‐equilibrial dynamics and species‐individualistic response to disturbance. Issue 6 (19th April 2021) - Woods, Kerry D.; Nagel, Thomas A.; Brzeziecki, Bogdan; Cowell, C. Mark; Firm, Dejan; Jaloviar, Peter; Kucbel, Stanislav; Lin, Yiching; Maciejewski, Zbigniew; Szwagrzyk, Jerzy; Vencurik, Jaroslav
Abstract: Aim: Old‐growth, mesic temperate forests are often assumed to be structured by gap‐phase processes, resulting in quasi‐equilibrial long‐term dynamics. This assumption influences management focused on simulation of natural disturbance dynamics and is embedded in most models of forest successional dynamics. We use multi‐decade monitoring of permanent plots in old‐growth forests to assess demographic assumptions directly with respect to tree mortality rates. Location: Sixteen sites in mesic, temperate old‐growth forests in eastern North America and Europe with multi‐decade monitoring. Time period: Variable across sites, spanning c . 20–78 years from 1936 to 2014. Major taxa studied: Tree species of late‐successional, cool‐temperate forests of Europe and eastern North America. Methods: We calculated and compared the annualized mortality rates ( m ), with confidence intervals, by species, size class and measurement interval, for tree species of sufficient abundance. Results: Retrospective analysis shows dynamic and diverse demographic properties across populations and sites. Stand‐scale mortality rates of 0.7–2.5%/year average higher than previous estimates for old‐growth temperate forests. Variations among species, over time and among size classes, suggest that gap‐phase models are inadequate to explain stand dynamics, implying instead that rare disturbance events of moderate severity have long‐lasting effects in old‐growth forests and that indirect anthropogenic influences affect old‐growth, unlogged forests. Main conclusions: Multi‐decade baseline data, essential for understanding community assembly and long‐term dynamics in these "slow systems, " are rare and poorly integrated. Our analysis demonstrates the value of the few long‐term, "legacy" data sets. Results suggest that differences in life history interact with complex disturbance histories, resulting in non‐equilibrial dynamics in old‐growth temperate tree communities, and that changes in disturbance patterns through anthropogenic climate change might, therefore, be an important driver of ecosystem change.